The effect of corporate governance, corporate social responsibility, and financial performance on tax avoidance - Sandhi Wiratmoko (The Indonesian Accounting Review, 2018)
This study aims to examine the effect of corporate governance, corporate social responsibility, and financial performance on tax avoidance. The dependent variable used in this study is tax avoidance as measured by Cash Effective Tax Rate (CETR), while the independent variables used are independent commissioners, audit committee, corporate social responsibility (CSR), debt ratio, and ROA. This study also uses firm size as the control variable. Population in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) and the Malaysia Stock Exchange (MYX) period 2012-2016. Sampling is conducted using purposive sampling method. The analysis technique used is multiple linear regression analysis. The results of this study show that in the sample of Indonesian manufacturing companies, the variables of independent commissioner, audit committee, and ROA have an effect on tax avoidance, while in the sample of Malaysian manufacturing companies, only the variables of debt ratio and ROA that have an effect on tax avoidance.